Anti-HER2 CD4+ T-helper type 1 response is a novel immune correlate to pathologic response following neoadjuvant therapy in HER2-positive breast cancer. Issue 1 (December 2015) - Datta, Jashodeep; Berk, Erik; Xu, Shuwen; Fitzpatrick, Elizabeth; Rosemblit, Cinthia; Lowenfeld, Lea; Goodman, Noah; Lewis, David; Zhang, Paul; Fisher, Carla; Roses, Robert; DeMichele, Angela; et al.
Abstract Introduction A progressive loss of circulating anti-human epidermal growth factor receptor-2/neu (HER2) CD4+ T-helper type 1 (Th1) immune responses is observed in HER2pos -invasive breast cancer (IBC) patients relative to healthy controls. Pathologic complete response (pCR) following neoadjuvant trastuzumab and chemotherapy (T + C) is associated with decreased recurrence and improved prognosis. We examined differences in anti-HER2 Th1 responses between pCR and non-pCR patients to identify modifiable immune correlates to pathologic response following neoadjuvant T + C. Methods Anti-HER2 Th1 responses in 87 HER2pos -IBC patients were examined using peripheral blood mononuclear cells pulsed with 6 HER2-derived class II peptides via IFN-γ ELISPOT. Th1 response metrics were anti-HER2responsivity, repertoire (number of reactive peptides), andcumulative response across 6 peptides (spot-forming cells [SFC]/106 cells). Anti-HER2 Th1 responses of non-pCR patients (n = 4) receiving adjuvant HER2-pulsed type 1-polarized dendritic cell (DC1) vaccination were analyzed pre- and post-immunization. Results Depressed anti-HER2 Th1 responses observed in treatment-naïve HER2pos -IBC patients (n = 22) did not improve globally in T + C-treated HER2pos -IBC patients (n = 65). Compared with adjuvant T + C receipt, neoadjuvant T + C — utilized in 61.5 % — was associated with higher anti-HER2 Th1 repertoire (p = 0.048). While pCR (n = 16) and non-pCR (n = 24) patients did not differ substantially in demographic/clinical characteristics, pCR patients demonstrated dramatically higher anti-HER2 Th1 responsivity (94 % vs. 33 %, p = 0.0002), repertoire (3.3 vs. 0.3 peptides, p < 0.0001), and cumulative response (148.2 vs. 22.4 SFC/106, p < 0.0001) versus non-pCR patients. After controlling for potential confounders, anti-HER2 Th1 responsivity remained independently associated with pathologic response (odds ratio 8.82, p = 0.016). This IFN-γ+ immune disparity was mediated by anti-HER2 CD4+ T-bet+ IFN-γ+ (i.e., Th1) — not CD4+ GATA-3+ IFN-γ+ (i.e., Th2) — phenotypes, and not attributable to non-pCR patients' immune incompetence, host-level T-cell anergy, or increased immunosuppressive populations. In recruited non-pCR patients, anti-HER2 Th1 repertoire (3.7 vs. 0.5, p = 0.014) and cumulative response (192.3 vs. 33.9 SFC/106, p = 0.014) improved significantly following HER2-pulsed DC1 vaccination. Conclusions Anti-HER2 CD4+ Th1 response is a novel immune correlate to pathologic response following neoadjuvant T + C. In non-pCR patients, depressed Th1 responses are not immunologically "fixed" and can be restored with HER2-directed Th1 immune interventions. In such high-risk patients, combining HER2-targeted therapies with strategies to boost anti-HER2 Th1 immunity may improve outcomes and mitigate recurrence.